20 years of NAFTA – trends in trade and the economic effects - Kowalik, Paweł (Economics of the 21st Century, 2014)
This year marks the twentieth anniversary of the largest economic grouping in history, both in terms of surface area and the generated GDP – the North American Free Trade Agreement – NAFTA. The grouping was established on 1 January 1994, with the objective of gradually doing away with the existing tariff and non-tariff barriers to trade between the United States, Canada, and Mexico. Its objectives and effects have long been under careful examination and subject to many analyses. Prognoses varied, from potentially significant benefits to anticipated losses, particularly for US economy. The paper is an attempt at presenting the twenty years of NAFTA operation, predominantly from the viewpoint of its impact on the trilateral trade exchange, unemployment, inflation, and the Gross Domestic Product (GDP) of its member states. The analyses suggest that NAFTA has proved its effectiveness in generating trade revenues for all its members, most notably for Mexico. However, its effects on individual income and employment were found to be marginal or, at best, moderate
Ekonomia XXI Wieku = Economics of the 21st Century, 2014, Nr 4 (4), s. 46-63
Keywords: NAFTA; economic integration; trade effects; cross-country comparative studies; integracja gospodarcza; efekty handlu; badania porównawcze krajów